The Dynamic Response of AuxHex and Star-Reentrant Honeycomb Cored Sandwich Panels Subject to Blast Loading - Ul Haq, Ahsan; Gunashekar, G.; Narala, Suresh Kumar Reddy (Arabian journal for science and engineering (2011), 2023)
In order to balance the blast protective performance and lightweight property, sandwich panels with various geometries of core are being employed in the military armours and modern-day combat vehicles. Owing to the superior energy absorption capacity of auxetic-reentrant cellular structures, hybridizing auxetic cells with the regular hexagonal cells in the honeycomb core for the purpose of blast protection could be a promising method. Therefore, novel honeycomb cores with combined auxetic and hexagonal cells (AuxHex and Star-Reentrant) are designed for blast protection panel with an aim to enhance the blast performance by improving the energy absorption and minimizing the dynamic deflection of the back plate. Initially, the dynamic response of honeycomb sandwich panels with various regular geometrical cores is analysed and validated with the experimental results from the literature. Further, air blast analysis has been performed on AuxHex and Star-Reentrant honeycomb cored sandwich panel having same relative density as that of hexagonal honeycomb core under exactly same conditions. In addition to that, the study is extended for varying charges of TNT and at different stand-off distances. It has been revealed that the sandwich panel with AuxHex and Star-Reentrant core of same relative density as that of hexagonal honeycomb core absorbs 28% and 19.2% more amount of energy and experiences 17% and 8% less deflection, respectively, than those with regular hexagonal honeycomb core.